The right to family life of foreigners in Spain: titration assay applicable regulations - Ezquerra Ubero, José Javier (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2016)
The objective of this paper is to assess the regulations applicable to family reunification in Spain. The analysis will focus in the general regulation system, but mention will also be made, for purposes of comparasion, to the more favourable regulation applicable to spanish families and to nationals of the other member states of the European Economic Space.